Comparison of Three Protocols for Tight Glycemic Control in Cardiac Surgery Patients - Blaha, Jan; Kopecky, Petr; Matias, Michal; Hovorka, Roman; Kunstyr, Jan; Kotulak, Tomas; Lips, Michal; Rubes, David; Stritesky, Martin; Lindner, Jaroslav; Semrad, Michal; Haluzik, Martin (Diabetes care, 2009)
OBJECTIVE: We performed a randomized trial to compare three insulin-titration protocols for tight glycemic control (TGC) in a surgical intensive care unit: an absolute glucose (Matias) protocol, a relative glucose change (Bath) protocol, and an enhanced model predictive control (eMPC) algorithm. RESEARCH DESIGN AND METHODS: A total of 120 consecutive patients after cardiac surgery were randomly assigned to the three protocols with a target glycemia range from 4.4 to 6.1 mmol/l. Intravenous insulin was administered continuously or in combination with insulin boluses (Matias protocol). Blood glucose was measured in 1- to 4-h intervals as requested by the protocols. RESULTS: The eMPC algorithm gave the best performance as assessed by time to target (8.8 ± 2.2 vs. 10.9 ± 1.0 vs. 12.3 ± 1.9 h; eMPC vs. Matias vs. Bath, respectively; P < 0.05), average blood glucose after reaching the target (5.2 ± 0.1 vs. 6.2 ± 0.1 vs. 5.8 ± 0.1 mmol/l; P < 0.01), time in target (62.8 ± 4.4 vs. 48.4 ± 3.28 vs. 55.5 ± 3.2%; P < 0.05), time in hyperglycemia >8.3 mmol/l (1.3 ± 1.2 vs. 12.8 ± 2.2 vs. 6.5 ± 2.0%; P < 0.05), and sampling interval (2.3 ± 0.1 vs. 2.1 ± 0.1 vs. 1.8 ± 0.1 h; P < 0.05). However, time in hypoglycemia risk range (2.9-4.3 mmol/l) in the eMPC group was the longest (22.2 ± 1.9 vs. 10.9 ± 1.5 vs. 13.1 ± 1.6; P < 0.05). No severe hypoglycemic episode (<2.3 mmol/l) occurred in the eMPC group compared with one in the Matias group and two in the Bath group. CONCLUSIONS: The eMPC algorithm provided the best TGC without increasing the risk of severe hypoglycemia while requiring the fewest glucose measurements. Overall, all protocols were safe and effective in the maintenance of TGC in cardiac surgery patients.